Inspecting How Different Students’ Personalities Affect Students' Performance in Calculus Practicum Courses Utilizing Peer Teaching Flipped Classroom Model - Ramadoni Ramadoni (Universitas Muhammadiyah Kalimantan Timur, 2023)
Calculus Practicum is an essential component of calculus courses. Calculus practicum is beneficial for enhancing calculus academic achievement by utilizing technology to accomplish calculus learning goals. Calculus is a concept that students must acquire through theory and practice. Students, on the other hand, are divided into two primary personality types: extroverts and introverts. The study process was influenced by students' personality types. The purpose of this research aimed to investigate the effect of students' personalities on their conceptual understanding abilities. Personality surveys and conceptual understanding assessments used as research instruments. According to research findings, students' conceptual understanding in calculus practicum courses is heavily influenced by personality category when employing the peer teaching flipped classroom model. Experiments such as peer teaching flipped classrooms demonstrate that extrovert students have superior conceptual understanding skills than introvert students. Creating videos and establishing class discussions has a big impact on extroverted students. They can deepen their skills while also sharing their information and understanding with their peers.